2005
DOI: 10.1182/blood-2004-11-4570
|View full text |Cite
|
Sign up to set email alerts
|

A phase-1 trial of bexarotene and denileukin diftitox in patients with relapsed or refractory cutaneous T-cell lymphoma

Abstract: Denileukin diftitox, a genetically engineered fusion protein combining the enzymatically active domains of diphtheria toxin and the full-length sequence for interleukin-2 (IL-2), efficiently targets lymphoma cells expressing the high-affinity IL-2 receptor (IL-2R) consisting of the ␣/p55/CD25, ␤/p75/CD122, and ␥/p64/ CD132 chains. In vitro studies demonstrated that the retinoid X receptor (RXR) retinoid, bexarotene, at biologically relevant concentrations of 10 ؊6 M to 10 ؊8 M, upregulated both the p55 and p75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(40 citation statements)
references
References 9 publications
0
40
0
Order By: Relevance
“…Interestingly, the retinoid X receptor retinoid, bexarotene, a new therapeutic agent for mycosis fungoides (34), up-regulates both the p55 and p75 subunits of IL-2R. This, in turn, enhances the susceptibility of the malignant cells to denileukin diftitox, resulting in overall response rates of 67% in relapsed CTCL patients (35).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the retinoid X receptor retinoid, bexarotene, a new therapeutic agent for mycosis fungoides (34), up-regulates both the p55 and p75 subunits of IL-2R. This, in turn, enhances the susceptibility of the malignant cells to denileukin diftitox, resulting in overall response rates of 67% in relapsed CTCL patients (35).…”
Section: Discussionmentioning
confidence: 99%
“…Bexarotene combined with denileukin diftitox provides a noteworthy example, as bexarotene was shown to increase IL-2Rb (CD122) expression in malignant T cells [232], conferring increased sensitivity to denileukin diftitox, thus forming the rationale for a phase I study combining these two agents [233]. In this study, 14 patients with relapsed/refractory CTCL received bexarotene (75-300 mg daily) with denileukin diftitox (18 mcg/kg daily for 3 days every 21 days).…”
Section: Bexarotenementioning
confidence: 99%
“…In this study, 14 patients with relapsed/refractory CTCL received bexarotene (75-300 mg daily) with denileukin diftitox (18 mcg/kg daily for 3 days every 21 days). Eight responses, including four complete responses, and upregulation of the IL-2 receptor following therapy were observed [233]. Future studies clarifying the optimal use of bexarotene, either in combination or sequentially with other agents, are needed.…”
Section: Bexarotenementioning
confidence: 99%
“…187 Fourteen patients with relapsed or refractory CTCL were treated with escalating doses of bexarotene (75-300 mg/d) and denileukin diftitox (18 mcg/kg/ d ϫ3 days every 21 days) had an overall response of 67% (4 complete responses, 4 partial responses). 187 The results of a multicenter phase III double-blind randomized trial of denileukin diftitox, recently published, showed significant response rates at both 9 and 18 mcg/kg dose levels compared with placebo controls in patients who had received Յ3 prior therapies. 188 Unfortunately, because of manufacturing issues, denileukin diftitoxin has been unavailable since fall 2011.…”
Section: Denileukin Diftitoxmentioning
confidence: 99%